Miedos al margen: representaciones de la violencia y la precariedad en Fuerzas Especiales de Diamela Eltit - Sandra Navarrete Barría (Les Cahiers ALHIM)
The aim of this article is to reflect about the social precariousness in Chile and the existence of what we’ve called “marginal fears”, in reference to the fears of the vulnerable population in this country, in the differents facets of their lives. We work on the novel Fuerzas Especiales (2013) by Diamela Eltit, which present an special treatment of this theme, since the perspective of a marginal subject and the constant abuse that she suffers by the police. The main questions are the following: ¿Can we talk about a group of fears that afflict the marginal population from Chile exclusevely? ¿Which would be the principal characterictics of these fears? ¿How do these fears dialogue with anothers fears in chilean society, like the collective fear to violence and crime? ¿What are the relations between marginals fears and the sturctural violence in this country? ¿Why does the author makes an issue of the fear since the perspective and the voice of a scarcity population?